2005
DOI: 10.1016/j.femsle.2004.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Intermedilysin release byStreptococcus intermedius: effects of various antibacterial drugs at sub-MIC levels

Abstract: Intermedilysin is a cytolytic toxin produced by Streptococcus intermedius, a pathogen of humans. In vitro studies showed that exposure of S. intermedius to sub-minimum inhibitory concentration (MIC) levels (1/2 MIC) of protein-inhibiting antibiotics and nucleic acid-inhibiting antibiotics decreased intermedilysin release by S. intermedius. The most potent antibiotic was clindamycin. On the other hand, exposure to cell wall-inhibiting antibiotics generally showed insignificant changes in intermedilysin release … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…However, in the postantibiotic treatment period in clinical therapy or in the environment, the antibiotic concentration is always lower than MIC. Such concentrations are defined as SICs, which are one of the major causes of drug resistance, although bacterial growth is not affected by antibiotics at SICs (Taylor et al, 2005;Martinez et al, 2009). In this study, we found that the Fig.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…However, in the postantibiotic treatment period in clinical therapy or in the environment, the antibiotic concentration is always lower than MIC. Such concentrations are defined as SICs, which are one of the major causes of drug resistance, although bacterial growth is not affected by antibiotics at SICs (Taylor et al, 2005;Martinez et al, 2009). In this study, we found that the Fig.…”
Section: Discussionmentioning
confidence: 70%
“…However, in the postantibiotic treatment period in clinical therapy or in the environment, the antibiotic concentration is always lower than MIC. Such concentrations are defined as SICs, which are one of the major causes of drug resistance, although bacterial growth is not affected by antibiotics at SICs (Taylor et al ., ; Martinez et al ., ). In this study, we found that the purple area in CV12472 was darker at the edge of the kanamycin inhibition zone, which prompted us to determine the mechanism involved in the antibiotic‐induced violacein production.…”
Section: Discussionmentioning
confidence: 97%
“…Clindamycin and azithromycin each displayed a relatively high level of in vitro antimicrobial activity against subgingival S. constellatus and S. intermedius , with only a low proportion of drug‐resistant strains identified in the present study. Clindamycin, in addition to its antimicrobial activity against S. intermedius , is also capable at sub‐MIC concentrations of markedly downregulating the organism's extracellular release of intermedilysin, a cytolytic toxin that may contribute as a virulence factor in S. intermedius –associated infections 32 …”
Section: Discussionmentioning
confidence: 99%
“…The ily gene was amplified using primer pair ILY-Fw (5GCAACTATCCAAAACAACAC-3) and ILY-Bw (5-GATTGTAGCCATTTCCACTC-3). 20 These were compared with nucleotide sequences on the BLAST website (www.ncbi.nlm.nih.gov/blast) to ensure the primer sequence. The strains were grown in tryptic soy broth and then incubated for 24 h with the MIC, subMIC, and MBC of kale; ampicillin, again used as the positive control; and tryptic soy broth, again used as the negative control.…”
Section: Gene Expression Studies For Antivirulence Efficiencymentioning
confidence: 99%